Sedimentology and Tectonic Setting of Sachun Formation in Folded Zagros Zone (SW Iran) - Mohammad Bahrami; Solmaz Arzaghi; Mohammad Sahraeyan (Institute of Advanced Engineering and Science, 2013)
The Sachun Formation (Paleocene- Lower Eocene), has been formed in Zagros basin, and has 1415 meters thickness in its type section. Sachun Formation sequence at the southern part of Kuh- E- Mianjangal, in Folded Zagros Zone in southwest of Iran, with a thickness of 580 meters was formed of two members. The Lower Member consists of about 280 meters thin to medium bedded of marl, marlstone and argillaceous, silty and sandy limestone with color of light gray to bluish gray, and associated with gypsum inter- layers, which are repeated continuously upward. In each of the alternations or cycles, the terrigenous grains size increase upward which is due to the depth decreasing in each cycle. The Upper Member consists of about 300 meters alternation of gypsum and marl, light gray to bluish gray associated with inter- layers of argillaceous and silty limestone. Microscopic studies of argillaceous limestone, in both members, have showed micrite and pelmicrite microfacies. No distinct fossils, either microscopic or macroscopic, are found in these members in the studied section. Sachun Formation facies have been deposited in a shallow depositional basin which has been controlled by a permanent sea level changes. Among the marine environments, peritdal environments show the most and the best correlation with the Sachun Formation facies. According to the sedimentary records, Sachun Formation has been deposited in a tectonically instable basin.